HOME REMEDIES FOR ORAL DISEASES - Selvam, *Rajeshwari; Ramesh Kumar, S.G; Narayanan, M.B.Aswath; Selvamary, A.Leena; Sujatha, A (International Journal of Ayurveda and Pharma Research, 2018)
Self-help through self-treatment makes a countless contribution. Home remedy use is a component of health self-management, particularly among people who have experienced limited access to medical care or discrimination by the health care system. Self-care using home remedies survived for long time and it surely give effect in the easiest, safest, fastest and cheapest way. Oral diseases are a significant public health burden in India as well as across the globe. The consequence of poor oral health deteriorates the individual health and wellbeing, decrease economic productivity, and act as significant risk factors for other systemic health ailments.  Developing countries have more diverse health systems than developed countries and expenditure in oral health care is low, access to Dental healthcare is limited and restricted to emergency Dental care or pain relief. Moreover, allopathic medicine is expensive and these chemicals can have adverse effects. Hence, there is a need for alternative products and natural extracts obtained from plants which are safe and biocompatible can be considered as good alternatives. In such circumstances use of home remedies would meet the need for treating minor ailments safely. Home remedies are good and comparable methods of equal value which have met the scientific and regulatory criteria for safety and effectiveness. The purpose of this review was to evaluate some of the commonly available foods being utilized in the treatment of oral diseases at home.